Is isokinetic shoulder strength a determinant of serve ball velocity in tennis? - Ölmez, C.; Hammami, N.; Apaydin, N.; Hattabi, S.; Sar, H.; Khezami, M. A.; Ince, A. (Sports Biomechanics, 2025)
The tennis serve is closely related to the quality of the tennis match. However, the isokinetic parameters associated with the tennis serve are still unclear. The aim of this study was to investigate the relationships between ball velocity and isokinetic shoulder strength in tennis serve and to determine isokinetic strength parameters that can predict tennis serve velocity. A total of 13 elite male athletes (16.8 ± 1.5 years) voluntarily participated in the study. The athletes` shoulder internal-external rotation, extension-flexion and abduction-adduction strengths were measured with 5-5-15 repetitions at 60°/s, 180°/s, 240°/s angular velocities. Later, the athletes` 1st, 2nd, and average serve ball speeds were determined using a handheld radar gun. Significant correlations were found between ball speed and isokinetic tennis serve strength (r = 0.556-0.819; p < 0.05). The correlations between ball speed and isokinetic strength performance were higher at 180°/s and 240°/s angular velocities. Extension (240°/s; r = 0.819), flexion (180°/s; r = 0.755), abduction (240°/s; r = 0.733), adduction (240°/s; r = 0.684) and internal rotation (180°/s; r = 0.803) were highly correlated with ball velocity. These findings suggest that strength training to increase the ball speed of the tennis serve should be performed fast at high angular velocities and planning should focus on the strength of extension, flexion, abduction, adduction and internal rotation.